Role of Lean Marketing of Marketing Superiority :An Analytical Study of Managers' Opinions in a Number of Mineral Water Factories in Erbil Governorate - Awrng Muhammad Muhyadden; Serwan Latef Haji (Zanco Journal of Human Sciences, 2026)
This study aims to examine the role of lean marketing in achieving marketing excellence through an analytical study of the opinions of managers in several mineral water factories in Erbil Governorate. The importance of the research lies in the fact that lean marketing is considered one of the modern trends in marketing thought, as it seeks to enable organizations to reduce waste, enhance operational efficiency, achieve customer satisfaction, and retain customers. The research problem is framed by the following main question: What is the role of lean marketing in achieving marketing excellence in mineral water factories in Erbil Governorate? The study adopted the descriptive-analytical method, and data were collected through a questionnaire distributed to managers in these factories. A total of 150 valid questionnaires were retrieved out of 180 distributed. The results of the statistical analysis revealed a significant correlation and impact between the dimensions of lean marketing (reducing defective products, minimizing excess inventory, eliminating unnecessary activities, reducing waiting time, minimizing unnecessary transportation, and continuous improvement) and marketing excellence. The findings also indicated that the application of lean marketing effectively contributes to enhancing the competitive capabilities of factories and achieving superior marketing performance in the market. The study concluded with several recommendations, the most important of which is ensuring top management commitment to adopting lean marketing and providing adequate financial and human resources for its effective implementation.